A concentric tube anchor system for fiber-reinforced polymer retrofit of reinforced concrete structural walls under extreme loads. Issue 1 (March 2018) - Lau, David T; Woods, Joshua E
In reinforced concrete elements strengthened with fiber-reinforced polymer sheets, premature debonding of the fiber-reinforced polymer from the concrete substrate occurs due to lack of anchorage, which reduces the efficiency of the retrofitting system. This article reviews several common anchor systems and describes the development, optimization, and testing of a steel tube anchor in retrofit of reinforced concrete structural elements using externally bonded fiber-reinforced polymer sheets suitable for application to improve resistance against extreme load conditions (e.g. blast, impact, or an earthquake). A detailed review of common anchor designs including the proposed tube anchor based on previous studies on flexure-dominated fiber-reinforced polymer-strengthened reinforced concrete shear walls is presented. In this study, finite element analysis is conducted to verify the observed behavior and better understand the deformation mechanisms of the tube anchor. Finite element modeling is then used to evaluate the influence of different design parameters on its performance and propose a design methodology that can be used to optimize the tube anchor design. To verify the performance of the optimized tube anchor, it is tested in an experimental program on the in-plane seismic strengthening of two shear-dominated squat walls strengthened using fiber-reinforced polymer sheets. Experimental results reveal that the optimized tube anchor performs well in preventing premature debonding and allows the fiber-reinforced polymer composite to achieve a higher level of strain when compared to an alternative anchor system. Finally, a set of design steps for the implementation of the tube anchor in fiber-reinforced polymer retrofit applications for reinforced concrete shear walls are presented.